Effect of North Atlantic Oscillation (NAO) on the Characteristics of Wave Patterns Affecting the Climate of Iraq - Ahmed Juad, Bushra (Al-Adab Journal, 2019)
The North Atlantic Oscillation (NAO) is an important climatic phenomenon. The phenomenon of NAO has a positive phase (positive pressure values) which becomes a negative phase (negative pressure values). The research concluded that the oscillation in its negative and the positive phases did not affect the frequency of trough and ridge and the number of days of duration and direction of its axes, did not show a certain trend in the repetition of wave characteristics, whether the negative or positive. However, there was a difference in the seasonal total of the troughs and ridges, which exceeded the frequency during the negative seasons, while the long waves and the system of trough + ridge were repeated between the negative and positive seasons. As for the number of days of survival, the number of days of survival was greater during the positive seasons and the fluctuations during the negative seasons.